The push out bond strength of bioceramic seal-er(Total Fill) after warm and cold obturation tech-niques An in vitro comparative - Batool B Mounes; Raghad Alhashimi (College of Dentistry/ University of Baghdad, 2022)
Background: The goal of a root canal treatment is three dimensional obturation with a complete seal of the root canal system. The aim of this study was to evaluate and compare the effect of two warm obturation techniques, warm vertical compaction (WVC) and, carrier based obturation technique Gutta Core (GC), versus two cold obturation techniques, cold lateral compaction (CLC) and, single cone (SC) on push-out bond strength of bioceramic sealer (Total Fill) at three different root levels. Materials and Methods: Forty extracted maxillary first molars teeth with a straight round palatal root canal and mature apices were selected for this study. After sectioning the palatal roots to 11 mm from the root apex, the canals were prepared with EDGEENDO X7 rotary system file from size 20 up to size 40 taper 04. The samples were then randomly separated into four groups based on obturation procedures (each group n = 10), with group A: obturated by WVC, group B: GC, group C: CLC, and group D: SC. Following obturation, the teeth were kept in an incubator at 37°C and 100% humidity for two weeks. Three slices of 2 mm thickness were cut horizontally at 2, 4.5, and 7 mm from the root apex in each of the three sections (apical, middle and coronal). The data were investigated using one-way ANOVA and Tukey's test with a significance level (p< 0.05). A digital microscope with a magnification of 60 X was used to establish the failure mode. Results: There was a significant increase in push-out bond strength following canal obturation with GC and WVC, particularly at the apical third (9.48, and 8.11 MPa, respectively) , compared to canals obturated with SC and CLC in all root levels except the middle third, at the (p< 0.05) significance level. The cohesive mode of failure was the most prevalent in all groups. Conclusio: BC (TotalFill) sealer showed higher bond strength when used in WVC and GC compared to other techniques. SC and CLC  were showed comparable bond strength values.